2014
DOI: 10.1039/c4ra03090g
|View full text |Cite
|
Sign up to set email alerts
|

Natural rubber for sustainable high-power electrical energy generation

Abstract: Sustainable natural rubber for soft generators opens up new possibilities for harvesting renewable resources. With this technology, ocean wave energy could become a cheap and clean resource for generation of electricity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
147
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(150 citation statements)
references
References 46 publications
3
147
0
Order By: Relevance
“…Parker also commercializes a thin elastomer film for EAPs, available on Amazon. For energy harvesting applications, natural rubber can be an interesting material (Kaltseis et al 2014) and can easily be purchased in long rolls (Fig. 2).…”
Section: Membrane Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parker also commercializes a thin elastomer film for EAPs, available on Amazon. For energy harvesting applications, natural rubber can be an interesting material (Kaltseis et al 2014) and can easily be purchased in long rolls (Fig. 2).…”
Section: Membrane Materialsmentioning
confidence: 99%
“…This higher voltage allows charges to be delivered to power an electrical load. In essence, a DE functions like a charge pump, transferring electrical charges from a low-electrical potential to a high-electrical potential, when it is mechanically stretched and relaxed (Kaltseis et al 2014).…”
Section: Principle Of Operationmentioning
confidence: 99%
“…Results of uniaxial and biaxial tests of VHB 4910 were reported in [26,23] and for silicone-based elastomers in [27]. Results of uniaxial tests of natural rubbers can be found in [28].…”
Section: Energy Harvesting 48mentioning
confidence: 99%
“…However, other DEs, in particular natural rubbers and polyurethanes (PUR), have been also investigated and demonstrated good potential for EH, in some cases better than VHB, e.g. [28,41,42]. One of the researches, [41], examined the influence of stretching on the electrical properties, such as the electrical (or dielectric) breakdown strength (DBS) and dielectric constant, of VHB 4910 and natural rubber and suggested that the latter had advantages over VHB in the context of EH.…”
Section: Energy Harvesting 48mentioning
confidence: 99%
“…where λ 1 denotes the stretch in direction 1 and λ 2 denotes the stretch in direction 2; Q is the charge accumulated on the surface of DE; A 0 = L 1 L 2 is the initial area of the DE, μ = 5.2 × 10 4 Pa [28] is the shear modulus; ε 0 ¼ 8:85 Â 10 À12 F=m and ε r ¼ 4:2 [28] denote vacuum permittivity and the relative permittivity of DE, respectively. The Maxwell stress in direction 3 can be expressed as…”
Section: Methodsmentioning
confidence: 99%